Comparative genomic analyses of the human fungal pathogens Coccidioides and their relatives - Sharpton, Thomas J.; Stajich, Jason E.; Rounsley, Steven D.; Gardner, Malcolm J.; Wortman, Jennifer R.; Jordar, Vinita S.; Maiti, Rama; Kodira, Chinnappa D.; Neafsey, Daniel E.; Zeng, Qiandong; Hung, Chiung-Yu; McMahan, Cody; et al.

(untitled) (Genome Research, 2009)
While most Ascomycetes tend to associate principally with plants, the dimorphic fungi Coccidioides immitis and Coccidioides posadasii are primary pathogens of immunocompetent mammals, including humans. Infection results from environmental exposure to Coccidiodies, which is believed to grow as a soil saprophyte in arid deserts. To investigate hypotheses about the life history and evolution of Coccidioides, the genomes of several Onygenales, including C. immitis and C. posadasii; a close, nonpathogenic relative, Uncinocarpus reesii; and a more diverged pathogenic fungus, Histoplasma capsulatum, were sequenced and compared with those of 13 more distantly related Ascomycetes. This analysis identified increases and decreases in gene family size associated with a host/substrate shift from plants to animals in the Onygenales. In addition, comparison among Onygenales genomes revealed evolutionary changes in Coccidioides that may underlie its infectious phenotype, the identification of which may facilitate improved treatment and prevention of coccidioidomycosis. Overall, the results suggest that Coccidioides species are not soil saprophytes, but that they have evolved to remain associated with their dead animal hosts in soil, and that Coccidioides metabolism genes, membrane-related proteins, and putatively antigenic compounds have evolved in response to interaction with an animal host.